2012
DOI: 10.1177/000348941212101204
|View full text |Cite
|
Sign up to set email alerts
|

Is Preoperative Computed Tomographic Density Measurement of Soft Tissues Helpful in the Diagnosis of Cholesteatoma?

Abstract: This study showed that the HU values on preoperative computed tomography did not suffice for the detection of cholesteatoma lesions. A clinician's physical examination together with an interpretation of computed tomography is still the "gold standard" method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…To increase the accuracy, we used the same value for the ROI surface area in every measurement. Despite our efforts, our results showed a fairly wide HU index distribution range, which is similar to the study by Lee et al, 12 who measured a ROI of 1.5 mm 2 and still demonstrated a wide variation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To increase the accuracy, we used the same value for the ROI surface area in every measurement. Despite our efforts, our results showed a fairly wide HU index distribution range, which is similar to the study by Lee et al, 12 who measured a ROI of 1.5 mm 2 and still demonstrated a wide variation.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, in a retrospective study published in 2012, Lee et al 12 measured the differences in the HU index in preoperative HRCT scans of COM and cholesteatoma patients. The sample was composed of 91 patients who underwent tympanomastoidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Shie et al proposed a feature-based classification system for otoscopic diagnosis of MEI, including, but not limited to, HIS features [ 21 ]. In a study including 91 patients, Lee et al concluded that measurements of Hounsfield units (HU)—i.e., HIS features—are not sufficient to distinguish between the two diseases [ 22 ]. Park et al, however, found HU values to be significantly different between cholesteatoma and inflammatory tissue in 82 patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-contrast-enhanced temporal bone computed tomography has its limitations with a soft tissue lesion and does not show any pathognomonic bony erosion pattern for cholesteatoma. The "gold standard" method adopted by clinicians for the accurate diagnosis of cholesteatoma is still combining a "detailed otologic history, physical examination of ears, and the temporal bone computed tomography findings interpretation" [39,40] . Echo-planar diffusion-weighted magnetic resonance imaging is also a valuable technique for cholesteatoma imaging [41] .…”
Section: Inflammation Statusmentioning
confidence: 99%